2020
DOI: 10.1002/vms3.256
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of the spike gene of porcine epidemic diarrhea viruses (PEDVs) circulating in Vietnam from 2015 to 2016

Abstract: Background Porcine epidemic diarrhea (PED) is a highly contagious swine disease caused by the PED virus (PEDV), which is a member of the family Coronaviridae . Since the first outbreaks in Belgium and the United Kingdom were reported in 1971, PED has spread throughout many countries around the world and causing significant economic loss. This study was conducted to investigate the recent distribution of PEDV strains in Vietnam during the 2015–2016 seasons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…In Vietnam, PEDV was first observed in the southern provinces in 2009 (21). Published studies have demonstrated that PEDV is present in all major swine-producing regions in Vietnam (21)(22)(23)(24)(25)(26). A descriptive survey recently provided evidence that northern Vietnam is an endemic area for PEDV, with a high proportion of PED-positive farms (30.89%) (Mai et al, unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam, PEDV was first observed in the southern provinces in 2009 (21). Published studies have demonstrated that PEDV is present in all major swine-producing regions in Vietnam (21)(22)(23)(24)(25)(26). A descriptive survey recently provided evidence that northern Vietnam is an endemic area for PEDV, with a high proportion of PED-positive farms (30.89%) (Mai et al, unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…PEDV was first reported in the south of Vietnam in 2009 [17]. From 2012 to 2016, PEDV strains belonging to the four classification groups circulated in many regions of Vietnam [33,34]. In this study, eight PEDV strains collected in Vietnam in 2018 were classified into three groups.…”
Section: Discussionmentioning
confidence: 96%
“…Vui et al (2015) has sequenced the first complete genome of PEDV from outbreaks in Vietnam in 2013 and suggested that the Vietnamese PEDV isolates were new variants. Other studies mainly focused on the spike gene sequences indicated that there have been remarkable changes in the Vietnamese PEDV strains collected from 2012 to 2016 (Kim et al, 2015;Diep et al, 2018;Than et al, 2020) and these may decrease the vaccine efficiencies. Although PEDV strains remain the main cause of piglet losses in large litters in Vietnam; however, very limited molecular data of their genotypic and genealogy of PEDV are available from Vietnam.…”
Section: Introductionmentioning
confidence: 99%